A Study of Primary Health Services in Tribal Areas in Himachal Pradesh - Sapna Devi (MultiTech Publisher, 2024)
Tribal areas in Himachal Pradesh face unique challenges in accessing primary health services due to their remote locations and distinct cultural practices. This study aims to understand the availability, accessibility, and quality of primary health services in these regions.The main goal of this research is to evaluate the state of primary health services in tribal areas of Himachal Pradesh and identify the barriers faced by the tribal population in accessing these services.The study was conducted using a mixed-methods approach. Data was collected through surveys and interviews with healthcare providers and residents of tribal areas. Additionally, visits to primary health centers and sub-centers were made to assess infrastructure and service delivery.The findings reveal significant gaps in healthcare infrastructure, a shortage of medical staff, and limited availability of essential medicines. Many tribal residents reported difficulties in accessing health facilities due to long distances and lack of transportation. Cultural factors and lack of awareness also contributed to the underutilization of available services.The study highlights the urgent need for improving healthcare infrastructure, increasing medical staff, and enhancing transportation facilities to ensure better access to primary health services in tribal areas of Himachal Pradesh. Tailored health awareness programs that respect cultural practices can also help in bridging the gap.